IL-4 Level in Rifampicin-Sensitive and Rifampicin-Resistant Lung Tuberculosis Patients - Joko Susanto; Jusak Nugraha; Soedarsono Soedarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Tuberculosis remains a global health burden. Mycobacterium tuberculosis infection causes humoral and cellular responses. Macrophages of patients with pulmonary tuberculosis evolve M1 polarization that blocks infection or immunosuppressive M2, promoting tissue repair mediated by IL-4, IL-10, and IL-13. Previous research showed a decrease of IL-4R and IL-10 expression in lung macrophages of anti-TB drug resistance. A molecular test can detect rifampicin- resistance. There has been no study, which showed the difference in serum IL-4 levels in rifampicin-sensitive and rifampicin-resistant tuberculosis patients. This study aimed to determine the difference between circulating IL-4 levels in rifampicin-sensitive and rifampicin-resistant pulmonary tuberculosis patients. This cross-sectional observational study consecutively recruited subjects based on positive molecular and acid-fast bacilli microscopic examination from MDR-TB Clinic of the Dr. Soetomo Hospital between December 2018 to March 2019. Subjects were classified into a rifampicin-sensitive and rifampicin-resistant group. On ELISA measurement, IL-4 data were analyzed with SPSS version 17. Mann-Whitney U test and ROC analysis tests were performed, and p < 0.05 was significant for Î±=0.05 (95% CI). There was significant difference between rifampicin-sensitive group (420±281 pg/mL) and rifampicin-resistant group (253±279 pg/mL) (p=0.014). Receiver operating characteristics analysis showed AUC 0.70, the sensitivity of 81.5%, the specificity of 63.6%, and the cut-off value of 235.6 pg/mL. There was a significantly higher level of circulating IL-4 in the rifampicin-sensitive group than the rifampicin-resistant group. IL-4 level in healthy subjects should be measured as the normal value in the population. Immunology and metabolic parameters should be performed to increase sample homogeneity. Further study was also needed to understand the IL-4 role in rifampicin resistance of lung tuberculosis patients in the Indonesia population.